Diverticulitis in the Young. (January 2015) - Kijsirichareanchai, Kunut; Mankongpaisarnrung, Charoen; Sutamtewagul, Grerk; Nugent, Kenneth; Rakvit, Ariwan
Background: Colonic diverticulitis is relatively uncommon in young patients, especially those younger than 40 years. We compared demographic data, clinical presentation, management, and clinical course of diverticulitis in patients ≤40 years old compared with patients >40 years old.Methods: This study included all patients who presented to the emergency department with a diagnosis of diverticulitis between October 1, 2009 and September 30, 2010. Patients were divided into 2 groups: group 1 (≤40 years old) and group 2 (>40 years old). Demographic characteristics, clinical presentation and management, and short-term outcomes were compared.Results: Ninety-four patients were included in the study (37 patients in group 1 and 57 patients in group 2). A higher percentage of obese and Hispanic men was found in group 1 ( P > .05). The rate of discharge from the emergency department was significantly higher in group 1 (56.8% in group 1 vs 7.0% in group 2, P < .01). Group 2 patients had a shorter median length of stay than group 1 patients (3.1 vs 5.7 days, P = .16). There were no differences in vital signs, laboratory data (including complete blood count and basic metabolic panel), and in-hospital mortality rates between the 2 groups.Conclusions: This study demonstrates that young Hispanic men develop diverticulitis and that this diagnosis needs to be considered when they present to emergency rooms with abdominal symptoms. A longitudinal study is needed to determine the long-term outcomes in these patients and to investigate the pathogenesis.